The conceptual framework of Islamic work ethic (IWE) / Norlela Kamaluddin and Siti Khadijah Ab. Manan. - Kamaluddin, Norlela; Ab. Manan, Siti Khadijah (Universiti Teknologi MARA Cawangan Selangor, 2010)
Current literature show that study on work ethics is gaining popularity among researchers for a very obvious reason namely moral hazard. Cases of corporate scandals and collapse provide evidence that moral misconducts among the employees contribute to the financial disaster of the company. Hence, it is believed that there is a possible relationship between work ethics and organisational performance. Nevertheless, the conducted studies are centred mainly on Protestant work ethic (PWE). Islamic Work Ethics (IWE) on the other hand, has been misunderstood or ignored in the field of management and organisation studies. This could be because management scholars have no ready access to the wealth of literature in Islam pertaining to IWE in business and organisation, although the fundamental principles have been in existence more than fourteen centuries ago. It is evidenced that Islam as a complete and comprehensive revealed Al-Deen (a way of life) has its universal set of work ethics that suit all people irrespective of race and religion. Hence, this paper tries to provide conceptually the shari’ah framework on IWE. The earlier work of Ali, A.J. will be used as a base of discussion. While the practical issues in IWE will not be discussed in this paper as a research study in future is needed to be conducted.